Ectoparasitic Syndemics: Polymicrobial Tick‐borne Disease Interactions in a Changing Anthropogenic Landscape. (14th December 2014) - Singer, Merrill; Bulled, Nicola
Abstract : Based on an assessment of the available research, this article uses syndemic theory to suggest the role of adverse bio–social interactions in increasing the total disease burden of tick‐borne infections in local populations. Given the worldwide distribution of ticks, capacity for coinfection, the anthropogenic role in environmental changes that facilitate tick dissemination and contact, evidence of syndemic interaction in tick‐borne diseases, and growing impact of ticks on global health, tick‐borne syndemics reveal fundamental ways in which human beings are not simply agents of environmental change but objects of that change as well.